AI Marketing Management and Data Privacy Compliance: Effects on Consumer Behavior and Loyalty - Yudilestari, Eka Putri; Setyaningsih, Istianah; Komara, Mutiara Andayani; Tarmudi, Tarmudi (Journal of Management and Business Innovations, 2025)
Artificial Intelligence (AI) has significantly transformed digital marketing within e-commerce. However, the effects of AI on customer loyalty, data ethics, and legal compliance are frequently examined in isolation, resulting in limited understanding of their combined influence in developing markets. This study investigates how AI-based marketing, ethical considerations, and legal regulations affect the loyalty of Shopee users in West Java, with a focus on Generation Z and Millennials. A survey of 120 individuals from the academic community in West Java was conducted, and multiple linear regression was employed to ensure analytical accuracy and reliability. The results indicate that AI-driven marketing, responsible data management, and adherence to legal regulations collectively enhance online customer loyalty. Notably, compliance with personal data protection laws emerged as the most influential factor in fostering loyalty. Although AI facilitates personalized marketing, regulatory clarity and transparency are the primary drivers of sustained user trust. The findings suggest that contemporary customer loyalty depends not only on technological innovation but also on transparent data practices and robust legal compliance. This research provides online businesses with foundational guidance for maintaining success through responsible conduct and the protection of user data. Keywords: Artifficial Intelligence, Customer Loyalty, Data Ethics, E-commerce, Legal Compliance